Tellurite-Dependent Blackening of Bacteria Emerges from the Dark Ages - Vasquez-Guzman, C (CSIRO, 2019)
The timeline of tellurite prokaryotic biology and biochemistry is now over 50 years long. Its start was in the clinical microbiology arena up to the 1970s. The 1980s saw the cloning of tellurite resistance determinants while from the 1990s through to the present, new strains were isolated and research into resistance mechanisms and biochemistry took place. The past 10 years have seen rising interest in more technological developments and considerable advancement in the understanding of the biochemical mechanisms of tellurite metabolism and biochemistry in several different prokaryotes. This research work has provided a list of genes and proteins and ideas about the fundamental metabolism of Te oxyanions. Yet the biomolecular mechanisms of the tellurite resistance determinants are far from established. Regardless, we have begun to see a new direction of Te biology beyond the clinical pathogen screening approaches, evolving into the biotechnology fields of bioremediation, bioconversion and bionanotechnologies and subsequent technovations. Knowledge on Te biology may still be lagging behind that of other chemical elements, but has moved beyond its dark ages and is now well into its renaissance. © 2019 CSIRO.